Cystic Meningioma in the Inter-Hemisferic Space Location - Muhammad Zafrullah Arifin; Firman Priguna Tjahjono; Agung Budi Sutiono; Ahmad Faried (Faculty of Medicine Universitas Padjadjaran, 2016)
Objective: The presentation of cystic meningioma in the inter-hemispheric near the falx cerebri is uncommon. It is difficult to differentiate it from intra-axial tumors, such as gliomas. Therefore, it is likely that it is misdiagnosed as other types of brain tumors.Methods: In this study, we reported a cystic meningioma case in the inter-hemispheric location, showing an intramural nodule on magnetic resonance imaging scans.Results: Patient underwent surgical treatment and pathological section confirmation revealing meningioma. The patient was a middle-age woman and had been misdiagnosed as suffering from glioma followed by slight hemipharesis on the right extremities.Conclusions: Although this is a rare case, it will be good if we always consider cystic meningioma in inter-hemispheric space when diagnosing this type of cystic lesion if the magnetic resonance imaging (MRI) shows a cystic lesion mimicking glioma image presentation.Keywords: Cystic meningioma, interhemispheric space, magnetic resonance imaging, diagnosis DOI: 10.15850/ijihs.v4n1.686